Incentive contracting when boards have related industry expertise - Nanda, Vikram; Onal, Bunyamin (Journal of Corporate Finance, 2016)
We posit that presence of informed directors, by enhancing the board's information and ability to advise and monitor management, will affect the nature of incentive contracts offered to CEOs. In particular, we study the effect of directors from related industries (DRIs) i.e., downstream or upstream industries: our premise is that DRIs contribute information about product-market prospects. Using a simple optimal-contracting model to develop testable predictions, we hypothesize that DRIs reduce a firm's reliance on stock-based incentives. Our empirical evidence is strongly supportive: CEO pay and replacements are less sensitive to stock performance, particularly when industry-related information is crucial and when stock price is less informative.